Spatial market integration in the EU beef and veal sector: policy decoupling and export bans - Rico Ihle; Bernhard Brümmer; Stanley R. Thompson (Georg-August-Universität Göttingen, Department für Agrarökonomie und Rurale Entwicklung (DARE), 2009)
The 2003 reforms of the Common Agricultural Policy of the Euro-pean Union allowed for discretionary implementation among member states. Discretion was allowed with respect to the timing and the degree of decoupling of policy support. Differences among member states were particularly apparent in the European beef and veal sector. Using weekly data from 2003 to 2009, we assess the consequences of different national implementation strategies of the reforms on market integration for young calves, which are intensively traded in the European Union. Time series properties are analyzed with a range unit-root test after which a multivariate cointegration model is estimated. We find that the calf markets in Germany, France, the Netherlands and Spain are integrated and tightly interrelated as evidenced by both short and long-run price transmis-sion. We also find strong statistical support for the hypothesis that decoupling reduced calf price levels. Additionally, we ascertain that the outbreak of the Blue Tongue disease induced a structural change in parts of the EU calf market. Using counterfactual scenarios, we provide an indication of the cost involved with granting member states such a high degree of discretion in implementation. We conclude that the national markets studied here belong to a common market.
Keywords: 330; 2003 CAP reform; calf market; decoupling; EU; market integration; price transmission